(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2010)
Methanol and aqueous extracts of Aerva lanata Linn Juss were taken for anthelmintic activity against Indian earthworm Pheritima postuma. Various concentrations of both extracts were tested and results were expressed in terms of time for paralysis and time taken for death of worms. Piperazine citrate (10 mg/ml) was used as reference standard and normal saline as a control group. Dose dependent activity was observed in both the extracts and the result shows that the methanol extract possesses more activity than aqueous extract and thus may be useful as an anthelmintic.